Morphological description of selected breeding line of Paphiopedilum: NRCO-P. lawrenceanum x P. ‘Winston Churchill’/2013/29 (IC-0614750) - Devadas, R.; Pattanayak, S. L.; Adhikari, M.; Singh, D. R. (Indian Journal of Hill Farming, 2017)
A superior breeding line (NRCO/PlxPw/2013/29) of Paphiopedilum progeny was identified and characterized that was developed using P. ‘Winston Churchill’ and Paphiopedilum lawrenceanum as parents. Inflorescence - solitary type with dominating flower size over the foliage. Moderately dense shiny purple colour hairs present on the surface of the peduncle, which is 20 cm length approximately. Flower size 13.2 x 14.2 cm with dominating yellow-green colour (RHSN144A) and strong dorsal sepal in white colour. Petals size (7.9 - 8.1 cm x 2.8 – 3 cm) broad oblong spathulate shape with roundish lobes at tips, unequal, upper margin undulated gradually from 1 to 6 number and bigger curves (from 7 to 11 no.), glabrous inside, broader tips are recurved upward (similar to P. villosum), median vein typical dark brownish purple colour (RHS187A). Lip bigger in size & broader and open type with yellow colour margin (RHS1A) from side lobes to frontal opening of lip that appear like lower beak of a bird (pointed curvature). Column short and staminode in half pentagonal in shape with protruded nose in yellow-orange colour (RHS 23B) in half-triangular shape and pointed downwards. It flowers during mid October to Mid February every year and regular in habit with 106 days potted vase life. The selected breeding line received national identity as IC-0614750 with NBPGR, New Delhi, India.